2013
DOI: 10.2298/vsp1304346r
|View full text |Cite
|
Sign up to set email alerts
|

Receptor activator of nuclear factor kappa B (RANK) as a determinant of peri-implantitis

Abstract: These results revealed association of increased RANK concentration in samples of peri-implant/gingival crevicular fluid with peri-implant inflammation and suggests that RANK could be a pathologic determinant of peri-implantitis, thereby a potential parameter in assessment of peri-implant tissue inflammation and a potential target in designing treatment strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 22 publications
1
13
0
Order By: Relevance
“…Additionally, one study showed that the TLR4 signaling pathway mediated the proinflammatory immune response to cobalt-alloy particles [35]. The level of the receptor activator of NF-κB was apparently increased in samples from patients with peri-implantitis compared with healthy implants [36]. The endotoxin LPS, a molecule found in the outer membrane of bacteria, can trigger stimulation of macrophages and microglial cells by activating various signal transduction pathways including NF-κB [37].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, one study showed that the TLR4 signaling pathway mediated the proinflammatory immune response to cobalt-alloy particles [35]. The level of the receptor activator of NF-κB was apparently increased in samples from patients with peri-implantitis compared with healthy implants [36]. The endotoxin LPS, a molecule found in the outer membrane of bacteria, can trigger stimulation of macrophages and microglial cells by activating various signal transduction pathways including NF-κB [37].…”
Section: Discussionmentioning
confidence: 99%
“…The important structural differences and the different local factors related to peri‐implant tissues may also render differences in the reliability of these biomarkers when used in the diagnosis of peri‐implant diseases 3,23,46 . Recent studies showed that higher levels of sRANKL, RANK, and OPG were associated with peri‐implantitis compared with healthy peri‐implant tissues, although the pattern of these biomarkers was also different when peri‐implantitis and periodontitis sites were compared 19,20 . Monov et al 13 reported no significant correlation between the measured sRANKL and OPG levels and clinical parameters, whereas Arikan et al 15 investigating the same biomarkers reported a significant correlation between OPG and BOP.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies evaluating bone loss (BL) biomarkers comparing patients with peri-implantitis and chronic periodontitis demonstrated a good level of recovery and significant correlations between measured markers and corresponding clinical parameters. 19,20 In these studies, an optimized working protocol was reported that demonstrated 100% detectability rate, and significant correlations with clinical parameters were reached for almost all parameters. After optimization of the working protocol, the next step in promoting biomolecule as biomarker is usually a cross-sectional study to profile the marker concentration under different tissue conditions.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…A prior study indicated that the NF-B concentration increased 1.5–4-fold in patients with peri-implantitis compared to those with mucositis (6). Moreover, recent studies demonstrated that high levels of NF-B were associated with peri-implantitis (40,41). In addition, NF-B is upregulated in inflammatory bowel disease and is a transcription regulator of the immune response (42).…”
Section: Discussionmentioning
confidence: 99%